Nauczycielki wobec możliwości zmiany pozycji społecznej przez uczniów. Klasowość w perspektywie ich osobistych teorii pedagogicznych - Dorota Duda (Problemy Wczesnej Edukacji)
In this article, I discuss early childhood education teachers’ attitudes towards possibilities of social mobility by pupils from lower-class background families. I problematise the issue of equality, discuss the opportunity for students’ social mobility within the school system, and introduce the teachers’ private pedagogical theories I identified during my PhD research. I have distinguished an emancipatory potential and an adaptive character of these, as well as subtypes of these theories.